2016
DOI: 10.1167/iovs.16-19285
|View full text |Cite
|
Sign up to set email alerts
|

VEGF as a Survival Factor in Ex Vivo Models of Early Diabetic Retinopathy

Abstract: These data show that protecting retinal neurons from diabetic stress also reduces VEGF expression and release, while inhibiting VEGF leads to exacerbation of apoptosis. These observations suggest that the retina in early DR releases VEGF as a prosurvival factor. Neuroprotective agents may decrease the need of VEGF production by the retina, therefore limiting the risk, in the long term, of pathologic angiogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
48
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(60 citation statements)
references
References 55 publications
9
48
0
1
Order By: Relevance
“…In retinal ischemia, VEGF decreases in a gradient from the RGC to the outer plexiform layer. With rapid damage to the RGCs, neuronal cell damage precedes capillary degeneration, Endothelial cell survival factors, including VEGF, are released by retinal neuronal cells, including RGCs [42, 43]. Thus another potential mechanism for enhanced survival of the retina in our study is the stimulation of VEGF production by retinal neurons.…”
Section: Discussionmentioning
confidence: 83%
“…In retinal ischemia, VEGF decreases in a gradient from the RGC to the outer plexiform layer. With rapid damage to the RGCs, neuronal cell damage precedes capillary degeneration, Endothelial cell survival factors, including VEGF, are released by retinal neuronal cells, including RGCs [42, 43]. Thus another potential mechanism for enhanced survival of the retina in our study is the stimulation of VEGF production by retinal neurons.…”
Section: Discussionmentioning
confidence: 83%
“…On the other hand, a recent study in retinal explants of mice demonstrated that VEGF prevents neuronal apoptosis shortly after exposure to various harmful stimuli frequent in diabetics including hyperglycaemia, AGEs and oxygen peroxide. However, this neuroprotective effect was eliminated when the ex vivo retinas were preincubated with a VEGF trapping protein or after many days of stimuli (Amato, Biagioni, Cammalleri, Dal Monte, & Casini, ). Thus, the following dilemma arises: How to correctly modulate VEGF levels in each patient in order to produce regression of neovascularization without inducing neuronal demise?…”
Section: Trophic Factorsmentioning
confidence: 99%
“…As previously reported, 1 µM OCT protects from apoptosis retinal explants exposed to OS (Amato et al, 2016). Similar to the dose-response experiment in HRECs, we performed an experiment in OS-treated retinal explants to assess the efficacy of decreasing concentrations of OCT and of MNP-OCT.…”
Section: Os-induced Apoptotic Cell Death In Retinal Explants Is Reducmentioning
confidence: 95%
“…Ex vivo cultures were prepared according to published protocols (Amato et al, 2016). Briefly, retinas were dissected, cut into four fragments and transferred onto Millicell-CM culture inserts (Merck Millipore, Burlington, MA, United States) with ganglion cells up.…”
Section: Retinal Explantsmentioning
confidence: 99%
See 1 more Smart Citation